Advertising sebagai Strategi Promosi dalam Mendorong Minat Menabung di Perbankan Syariah - Sari, Melida; Mustika Riantina, Eka (Kartika: Jurnal Studi Keislaman, 2024)
This study focuses on the role of advertising in enhancing saving interest within Islamic banking. The research emphasizes three main aspects: education based on Islamic values, the utilization of both digital and conventional promotional media, and message consistency in building a positive image of Islamic banks. A quantitative approach was employed by distributing questionnaires to respondents comprising both current and prospective customers of Islamic banking. The collected data were analyzed using descriptive and inferential statistical techniques to measure the influence of promotional variables on saving interest. The findings indicate that promotional content emphasizing Islamic values plays a significant role in increasing public understanding of the advantages of Islamic banks compared to conventional banks. The integrated use of digital and conventional media effectively expands the reach of promotional messages, particularly among younger generations who are more adaptive to technology. Moreover, message consistency contributes positively to shaping the credible and trustworthy image of Islamic banks. Overall, integrated promotional strategies are proven to enhance public saving interest in Islamic financial institutions. These findings suggest that promotion in Islamic banking goes beyond the mere delivery of information. It also serves as a public educational tool that strengthens awareness, trust, and customer loyalty toward Islamic financial institutions.